Simulation of Tidal Inundation along the Northern Coast of Central Java (Pantura) using GISBased Analysis - Hilma Wasilah Robbani; Adelia Nur Isna Kartikasari; Vanadani Pranantya; Niswah Selmi Kaffa (Geoid, 2025)
The northern coast of Java Island (locally known as Pantura) is a strategically important area, particularly in the distribution sector. However, its topographical characteristics and proximity to the Java Sea make it vulnerable to the threat of tidal inundation. Moreover, environmental factors such as sea level rise, land subsidence, and coastal abrasion further exacerbate its susceptibility to flooding. The phenomenon of tidal inundation, locally referred to as rob, occurs when seawater overflows onto low-lying coastal areas during high tides. The rob phenomenon significantly impacts the socio-economic conditions of coastal communities, disrupting daily activities and damaging critical infrastructure. This study simulates potential inundation using a uniform Highest High Water Level (HHWL) scenario of 1.2 meters to estimate flood depth and spatial extent. The modeling approach applies a consistent water surface elevation across the study area, without considering storm surge and hydrodynamics, resulting in generalized inundation patterns. The methodology follows the Technical Guidelines for Disaster Risk Assessment issued by Indonesia’s National Disaster Management Agency (BNPB) and integrates various spatial datasets, including land cover data from Sentinel Land Cover by ESRI, topographic data from the Shuttle Radar Topography Mission (SRTM), Digital Elevation Model (DEM), and maximum tidal height data processed using the Admiralty method. The analysis shows that, assuming a Highest High Water Level of 1.2 meters, Kendal Regency, Brebes Regency, and Semarang City are the most affected areas in terms of both flood depth and extent. The inundated areas are estimated at 3,744.91 hectares in Kendal Regency, 2,880.58 hectares in Brebes Regency, and 513.17 hectares in Semarang City. This situation could become more severe in the event of storm surge, extreme weather, or climate anomalies if timely and effective mitigation measures are not implemented. These findings are expected to provide a strong foundation for policymakers to formulate targeted, data-driven, and sustainable mitigation strategies to protect communities and infrastructure along Java’s northern coastal region.